Physical properties and core-log seismic integration from drilling at the Danube deep-sea fan, Black Sea. (April 2020) - Riedel, M.; Freudenthal, T.; Bergenthal, M.; Haeckel, M.; Wallmann, K.; Spangenberg, E.; Bialas, J.; Bohrmann, G.
Abstract: Drilling, coring, and geophysical logging were performed with the MARUM-MeBo200 seafloor drilling rig to investigate gas hydrate occurrences of the Danube deep sea fan, off Romania, Black Sea. Three sites within a channel-levee complex were investigated. Geophysical log data of P-wave velocity, electrical resistivity, and spectral gamma ray are combined with core-derived physical properties of porosity, magnetic susceptibility, and bulk density. Core- and log physical property data are used to define a time-depth conversion by synthetic seismogram modeling, which is then used to interpret the seismic data. Individual polarity reversed reflectors within the stratigraphic column drilled are linked to reduction in P-wave velocity and bulk density. Those reflectors (and associated reflection packages) are accompanied by distinct and systematic changes in sediment porosity, magnetic susceptibility, and electrical resistivity. Overall, the sediments at drill site GeoB22605 (MeBo-17) represent the younger (upper) levee sequence of the channel, that has been eroded at drill site GeoB22603 (MeBo-16). Splicing seismic data across the channel from the East (MeBo-16) to the West (MeBo-17) demonstrates the continuation of reflectors underneath the channel. The upper 50 m below seafloor (mbsf) at site MeBo-16 do not stratigraphically belong to the same sequence of the (deeper) levee-deposits. Above the marked erosional unconformity, sediments at Site MeBo-16 are likely derived by a mixture of repeated slump-events (identified as seismically transparent units) interbedded with hemi-pelagic sedimentation. Similarly, sediments within the upper 20 mbsf at Site MeBo-17 are not stratigraphically the same levee-deposits, but are derived by a mixture of slump-events (also seen in the marked seafloor amphitheatre architecture of a large failure complex extending further upslope) and hemi-pelagic sedimentation. All observations combined show that the seismically observed stratigraphic pattern represents a reflectivity sequence mostly driven by variations in density (porosity) and correspondingly by changes in P-wave velocity and electrical resistivity. Observations from the geophysical log- and core, as well as geochemical data, show no evidence for the presence of any significant gas hydrates within the drilled/cored sequences. Highlights: Physical properties obtained from core and log data at the Danube deep sea fan are reported. Core-log-seismic integration defines stratigraphic framework at the S2 channel. All data suggest no gas hydrate is present at drill sites within uncertainties of methods employed.